Species composition of birds in Menchali Forest Reserve and Bukit Ridan Forest Reserve at Rompin, Pahang - Mahiyuddin, Sharifah Nur Ain (2016)
Forest condition would affect the species composition of birds. Little info on bird’s population is available in the forest. The objectives of this study were to compare the species composition, species diversity, species richness, species evenness of birds in lowland forest of Menchali Forest Reserve and hill forest of Bukit Ridan Forest Reserve. The methods used were transect survey in Menchali Forest Reserve and bird netting in Bukit Ridan Forest Reserve. The results of the study showed that Menchali Forest Reserve has higher species composition than Bukit Ridan Forest Reserve. Similar results were observed for species diversity and species richness. In term of species evenness, the species were distributed more evenly in Bukit Ridan Forest Reserve than Menchali Forest Reserve. Overall the species that have been recorded were 38 species of birds from 28 falimies which is 30 species from 20 families in Menchali Forest Reserve and eight species which represented by six families in Bukit Ridan Forest Reserve. In Menchali Forest Reserve, two near threatened species,Treron fulvicollis and Eurylaimus ochromalus have been recorded.The study showed that Menchali Forest Reserve can be classified as a good forest condition.